Incidence and Risk Factors of Velopharyngeal Insufficiency Postadenotonsillectomy. (24th July 2015) - Khami, Maria; Tan, Susan; Glicksman, Jordan Thomas; Husein, Murad
Abstract : Objectives: To evaluate the incidence and risk factors of velopharyngeal insufficiency (VPI) postadenoidectomy, posttonsillectomy, and postadenotonsillectomy. Study Design: Retrospective chart review. Setting: Academic tertiary care center (2007‐2014). Subjects and Methods: Retrospective review of patients who underwent adenoidectomies, tonsillectomies, or adenotonsillectomies by 1 pediatric otolaryngologist. Patient's age, sex, type of surgery, indication for surgery, medical syndromes, tonsil grade, adenoid size, and pre‐ and postoperative nasal air emissions were obtained. Results: The VPI risk at 3 weeks postoperatively was 13.6% (95% CI: 9.0%, 18.2%) for adenotonsillectomies, 3.2% (95% CI: 1.2%, 7.6%) for adenoidectomies, and 2.2% (95% CI: 2.1%, 6.5%) for tonsillectomies. There was a significantly higher risk of VPI with combined procedures in comparison with adenoidectomies ( P =. 02) or tonsillectomies alone ( P =. 03). There was no significant difference in risk of VPI between adenoidectomies and tonsillectomies ( P =. 78); between surgical indication groups (sleep‐disordered breathing vs other; P =. 15); or in terms of sex ( P =. 80), age ( P =. 11), tonsil grade ( P =. 96), or adenoid size ( P =. 15). There was no qualitative difference in postoperative nasal air emissions between patients with and without medical syndromes. Conclusion: Our data are consistent with the literature that most VPI after adenotonsillectomy is temporary in nature and resolves by 5 months postoperatively. Combined procedures were shown to have a significantly higher risk of VPI. Our rates of VPI were much higher than that previously cited and may be indicative of subclinical cases of VPI, which were accounted for due to this study's unique methodology.